Acute oral administration of the novel, competitive and selective glucocorticoid receptor antagonist ORG 34517 reduces the severity of ethanol withdrawal and related hypothalamic- pituitary-adrenal axis activation - Reynolds, Anna R. (Drug Alcohol Depend, 2015)
BACKGROUND: The development of ethanol dependence is associated with alterations in hypothalamic-pituitary-adrenal (HPA) axis and activation of type II glucocorticoid receptors (GR). These effects may contribute to withdrawal-associated anxiety, craving and relapse to drinking. The present studies examined acute and oral administration of the novel, selective and competitive GR antagonist ORG 34517 on the severity of ethanol withdrawal. METHODS: Adult, male Sprague-Dawley rats were administered ethanol (4g/kg/i.g.) twice daily for 5 days followed by 2 days of withdrawal for 1, 2 or 3 consecutive cycles. Blood ethanol levels (BELs) were determined at 0930 on Day 4 of each week, while blood corticosterone levels (BCLs) were obtained at 1100 hrs on the first day of each ethanol withdrawal. During early withdrawal, subjects received oral administration of ORG 345617 (60 mg/kg/i.g.) or a placebo and withdrawal was monitored. RESULTS: Peak BELs of 225.52 mg/dl were observed during the third week. Withdrawal from three cycles of the regimen produced marked behavioral abnormalities (e.g. aggression, rigidity, and hypoactivity) and significant increases in BCLs of ethanol-dependent subjects. Acute, oral administration of ORG 34517 during early withdrawal significantly reduced both the severity of ethanol withdrawal, as reflected in reduced rigidity, aggression, and hypoactivity, and elevations in BCL without producing any sedative-like effects. CONCLUSIONS: The present findings demonstrate that repeated ethanol exposure and withdrawal is associated with significant behavioral abnormalities and dysregulation of HPA axis activation. Further these data suggest that selective GR antagonists should be further considered as putative pharmacotherapies for treatment of ethanol dependence.